Citizen Science in Schools: Students Collect Valuable Mammal Data for Science, Conservation, and Community Engagement. (12th December 2018) - Schuttler, Stephanie G; Sears, Rebecca S; Orendain, Isabel; Khot, Rahul; Rubenstein, Daniel; Rubenstein, Nancy; Dunn, Robert R; Baird, Elizabeth; Kandros, Kimberly; O'Brien, Timothy; Kays, Roland
Abstract: Citizen science has been touted as an effective means to collect large-scale data while engaging the public. We demonstrate that children as young as 9 years old can collect valuable mammal monitoring data using camera traps while connecting with nature and learning through their own scientific discoveries. Indian, Kenyan, Mexican, and American students used camera traps near their schools and detected 13–37 species, all of which were verified by professionals. These data describe rich mammal faunas near schools, sometimes surpassing nearby protected areas, and included five endangered species. Ninety-four percent of the camera traps were set in accordance with scientific protocols, and the teachers reported the experience as highly engaging for their students. Furthermore, the generated photos and results had community-wide impacts involving local politicians, community members, and the media. We show that children can run sensors to contribute valid scientific data important for conservation and research.